Keats’ “Lamia:” the serpentine dialectic - Pekgöz, Kürşat K. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
This thesis is an attempt to disentangle the serpentine dialectic of Keats’ “Lamia.” I am positing three transformations in the development of the mixoparthenos figure: monstrous mother, a cannibalistic and vampiric phantom, and a tragic character. All three layers of myth are fully present in Keats’ poem, but Lamia is ultimately more tragic than monstrous. I also posit that Keats’ version of the story is more sympathetic to the she-serpent at least partly because Keats, unlike Plato, values imagination over reason.